Compositions and microstructures of CB sulfides: Implications for the thermal history of the CB chondrite parent body. (26th July 2017) - Srinivasan, Poorna; Jones, Rhian H.; Brearley, Adrian J.
Abstract: We studied textures and compositions of sulfide inclusions in unzoned Fe, Ni metal particles within CBa Gujba, CBa Weatherford, CBb HH 237, and CBb QUE 94411 in order to constrain formation conditions and secondary thermal histories on the CB parent body. Unzoned metal particles in all four chondrites have very similar metal and sulfide compositions. Metal particles contain different types of sulfides, which we categorize as: homogeneous low‐Cr sulfides composed of troilite, troilite‐containing exsolved daubreelite lamellae, arcuate sulfides that occur along metal grain boundaries, and shock‐melted sulfides composed of a mixture of troilite and Fe, Ni metal. Our model for formation proposes that the unzoned metal particles were initially metal droplets that formed from splashing by a partially molten impacting body. Sulfide inclusions later formed as a result of precipitation of excess S from solid metal at low temperatures, either during single stage cooling or during a reheating event by impacts. Sulfides containing exsolution lamellae record temperatures of ≪600 °C, and irregular Fe‐FeS intergrowth textures suggest localized shock melting, both of which are indicative of heterogeneous heating by impact processes on the CB parent body. Our study shows that CBa and CBb chondrites formed in a similar environment, and also experienced similar secondary impact processing.